A proposed integrated cash waqf micro enterprise investment (ICWME-I) model for mitigating the financial and human capital development challenges of micro enterprises in Malaysia - Mohamed Asmy bin Mohd Thas Thaker (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2015)
This study has developed an Integrated Cash Waqf Micro Enterprise Investment (ICWME-I) Model that is aimed at enhancing financial and human capital development services for micro enterprises. In this model, Cash Waqf Institution (CWI) – an established separate entity of SIRCs or corporate sector will raise Cash Waqf fund in the form of real money and Waqf Certificate. CWI will equally provide financial services to micro enterprises by forming Musharakah Mutanaqisah (Diminishing Partnership) arrangement. Furthermore, prior to obtain financial services from CWI, micro enterprises have to join the human capital development programmes provided by CWI. CWI will provide training centre that offers various kinds of training programmes to equip them with various skills related to micro enterprises. Thus, this model suggests ways of improving and meeting the need of micro enterprises in Malaysia by providing affordable financial and human capital development services. The study uses mixed method (interview and survey) approach. The interview was conducted to validate ICWME-I Model in terms of its suitability, applicability and the prospects. The findings from interviews reveal that the experts have positive perception and attitudes towards the proposed ICWME-I Model. Besides, the experts opine that ICWME-I Model is applicable in Malaysia and has tremendous benefits for micro enterprises. Similarly, the results from survey, analysed using Structural Equation Modeling (SEM) based on Theory of Reasoned Action (TRA) hypothesize that behavioral intention of micro enterprises to use ICWME-I Model is significantly and positively impacted by the attitude and subjective norm of micro enterprises. This thus suggests that when the micro entrepreneurs have a more positive view about the outcome of ICWME-I Model, the more favourable their attitude toward the behavior and subsequently, the stronger their intention to use ICWME-I Model to finance their businesses and also for human capital development. Besides, it is believed that the social pressure groups that assert subjective norms, including family members, relatives, friends, neighbour and co-workers, influence the decision making process for micro enterprises who are interested in using ICWME-I Model in the future.